Pengembangan Kelompok Belajar Paket B - M. Sardjan Kadir (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
Developing Learners Group through Package B. This action research aimed at developing a program that would involve learners in the learning activities of Package B until they finished the program, which is equal to junior high school, and that would develop learners’ creativity and personality. The study was intended for three years, starting from 1996. However, it was conducted yearly in accordance with the research fund. In 1996’1997, Package B developed a program which make learners engaged in the learning activities. The program was projected to help them finish the package for three years to get an academic qualification equal to junior high school. In addition, it helped them develop their creativity and personality through making educational toys and printing.